2022
DOI: 10.1002/ceat.202200375
|View full text |Cite
|
Sign up to set email alerts
|

How Wetting Properties Influence the Wear of Radial Lip Sealing Systems

Abstract: Increased wear on radial lip seal systems is observed when sealing modern lubricants, such as polyglycols and esters. This can impair the function of the sealing system and ultimately lead to leakage. This work, carried out within the AiF research project ''Welleneinlauf'' (wear of counter faces) [1], shows methods to identify and predict excessive wear of radial lip sealing systems based on their wetting properties and pumping rate. The knowledge gained will support users by providing faster and more cost-eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…It has been shown that better lubricant wetting of a surface contributes to improved friction properties. 7 Improved wetting of a liquid lubricant on aluminum surfaces can be achieved either by reducing the surface tension or viscosity of the lubricant, or by increasing the surface energy of the aluminum sheet. There have been studies to modify the lubricant composition to improve lubricant spreading on the surface, 8,9 with some successful results in reducing friction and wear.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that better lubricant wetting of a surface contributes to improved friction properties. 7 Improved wetting of a liquid lubricant on aluminum surfaces can be achieved either by reducing the surface tension or viscosity of the lubricant, or by increasing the surface energy of the aluminum sheet. There have been studies to modify the lubricant composition to improve lubricant spreading on the surface, 8,9 with some successful results in reducing friction and wear.…”
Section: ■ Introductionmentioning
confidence: 99%
“…It has been shown that better lubricant wetting of a surface contributes to improved friction properties . Improved wetting of a liquid lubricant on aluminum surfaces can be achieved either by reducing the surface tension or viscosity of the lubricant, or by increasing the surface energy of the aluminum sheet.…”
Section: Introductionmentioning
confidence: 99%